Motif Bantuan Australia Terkait Isu Perubahan Iklim Di Pasifik Selatan Pada Masa Pemerintahan Scott Morrison - Humaira, Raysha; Moenir, Haiyyu Darman (Hubungan Internasional Universitas Andalas, 2023)
This article analyzes Australia's motives under Scott Morrison's administration regarding its climate fund for the South Pacific countries. Under Scott Morrison's leadership, Australia has been fundamentally skeptical about climate change issues, such as his policy of developing the coal and gas industries, which produce high emissions, until it withdrew as a global climate fund donor. On the other hand, Australia increased its climate fund, especially in the South Pacific region. This research used a qualitative method with a descriptive analysis approach. The data was collected through library research and then analyzed using the concept of foreign aid motives developed by John Degnbol-Martinussen and Poul Engberg-Pedersen. This study found that, behind moral and humanitarian motives, there are Australia's efforts to reduce poverty levels in the South Pacific region caused by climate change. Through political motives, it found that this climate fund was used as Australia's strategy in its battle with China to gain influence and improve security in the South Pacific region. Meanwhile, the environmental motive is based on the responsibility to help mitigate and adapt to climate change in developing countries. Based on these findings, political motives became the dominant and most significant motives behind Australia's climate fund for the South Pacific countries.